2021
DOI: 10.3389/fonc.2021.777686
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Immune Checkpoint Inhibitor in Advanced Esophageal Squamous Cell Carcinoma: A Meta-Analysis

Abstract: BackgroundThe published evidence from several randomized controlled clinical trials of immunotherapy for advanced esophageal squamous cell carcinoma has shown promising results. This study aimed to investigate the efficacy and safety of immune checkpoint inhibitor treatment in esophageal squamous cell carcinoma.MethodsPubMed, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles published before December 30, 2020. The data for efficacy and safety of immune checkpoint inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although ICB has revolutionised ESCC therapeutics, not all patients gain clinical benefits from these treatments, 50 which raises the question of whether the spatial ITH is responsible for these differences. This study utilised emerging DSP technology to address the AOIs of specific tumours and stroma and to assess the fundamental molecular nature of our ESCC cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ICB has revolutionised ESCC therapeutics, not all patients gain clinical benefits from these treatments, 50 which raises the question of whether the spatial ITH is responsible for these differences. This study utilised emerging DSP technology to address the AOIs of specific tumours and stroma and to assess the fundamental molecular nature of our ESCC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Unprecedented advances have been made in ESCC treatment with the application of immune checkpoint blockade (ICB). 49,50 However, immunomodulators and the immune cell repertoire have not been well characterised in ESCC, particularly in the subregions of the primary tumour (PT sup and PT deep ) and matched LN met . First, we focused on the expression of the 33 immunomodulatory genes associated with cancer immunity (Table S12).…”
Section: Spatial Heterogeneity Of Rna Profiles and Tme In Esccmentioning
confidence: 99%
“…Cancer treatment requires ongoing monitoring and flexible strategies, which might be lacking in these lower-tier institutions. 59,60 Nonetheless, the 37.5% discount could benefit patients with mobility issues, those living in remote locations, or those without insurance coverage for this treatment, as they might opt for a more affordable medication and comprehensive treatment at primary health care institutions.…”
Section: Discussionmentioning
confidence: 99%
“…e most common Grade ≥3 treatment-related adverse events (TRAEs) were anemia, asthenia, rash, fatigue, anorexia, diarrhea, pneumonia, neutropenia, and vomiting. Patients receiving ICIs had a decreased risk of TRAEs (relative risk: 0.82, 95% CI: 0.62-1.08; P < 0.001) and Grade ≥3 TRAEs (RR: 0.50, 95% CI: 0.42-0.60; P < 0.001) compared with those undergoing CT. [26] IO IN SUBSEQUENT LINES e large Phase 2 expansion cohort of the KEYNOTE-059 trial reported results for pembrolizumab in 259 patients with gastric or EGJ adenocarcinoma. is international multicenter trial enrolled equal proportions of patients with gastric (48.3%) and EGJ cancers (51.4%).…”
Section: In Esccmentioning
confidence: 99%